2021
DOI: 10.1016/j.psj.2021.101389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing hydroxy selenomethionine on meat quality of yellow feather broiler

Abstract: This study was conducted to evaluate the effect of supplementing hydroxy selenomethionine ( OH-SeMet ) on performance, selenium ( Se ) deposition in the breast muscle, quality and oxidative stability, and expression of selenoprotein encoding genes of breast meat of the native slow-growing yellow-feathered broiler birds. A total of 375 one-day-old local yellow male birds were randomly assigned into 5 dietary treatments, supplemented with Se 0.0, 0.2, 0.4, 0.6, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…However, Ile supplementation significantly improved growth performance of broilers fed a LPD, partially in agreement with a previous study that reported significantly increased ADG and decreased F:G of broilers fed a diet supplemented with Ile ( Corrent and Bartelt, 2011 ). Chicken meat is an excellent source of animal protein for human nutrition, thus meat quality is especially important to the consumer ( Tang et al, 2021 ). The pH is an important parameter of meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ile supplementation significantly improved growth performance of broilers fed a LPD, partially in agreement with a previous study that reported significantly increased ADG and decreased F:G of broilers fed a diet supplemented with Ile ( Corrent and Bartelt, 2011 ). Chicken meat is an excellent source of animal protein for human nutrition, thus meat quality is especially important to the consumer ( Tang et al, 2021 ). The pH is an important parameter of meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the addition of selenium yeast and jujube powder to the diet can significantly reduce the MFI and increase the shear force of chicken breast after slaughter, which is consistent with the research of Vieira et al (2021) , this may be because the supplementation of natural antioxidants such as selenium yeast and jujube powder in the diet inhibited the activity of apoptotic enzymes and thus inhibited the degradation of chicken myofibrils by other means. However, studies have also shown that basal diets supplemented with different concentrations of selenium (in the form of hydroxy-selenomethionine) reduced postmortem shear stress in yellow feathered broilers ( Tang et al, 2021 ). Unlike the changes in chicken tenderness in this study, this may be because the type of chicken and the basal diet lead to differences in the experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al . (2021) studied the effect of adding hydroxy selenomethionine (OH‐SeMet) on the meat quality of yellow‐finned broiler chickens. They found that adding OH‐SeMet to the feed improved the water retention capacity, tenderness of breast muscle and meat quality.…”
Section: Characteristics Of Selenoproteinsmentioning
confidence: 99%
“…When the Se concentration was 60 mg/kg in the nutritional evaluation of Se-enriched mushroom protein by the RC method, the chemical score, essential amino acid index, biomass value, nutritional index and essential amino acid content of selenoproteins were all improved compared to the nonenriched group, indicating that selenoproteins have higher nutritional value than the control group of proteins. Tang et al (2021) studied the effect of adding hydroxy selenomethionine (OH-SeMet) on the meat quality of yellow-finned broiler chickens. They found that adding OH-SeMet to the feed improved the water retention capacity, tenderness of breast muscle and meat quality.…”
Section: Nutritional Valuementioning
confidence: 99%